2014
DOI: 10.1080/00223891.2014.889024
|View full text |Cite
|
Sign up to set email alerts
|

Overriding “Doing Wrong” and “Not Doing Right”: Validation of the Dispositional Self-Control Scale (DSC)

Abstract: We present the Dispositional Self-Control (DSC) Scale, which reflects individuals' tendency to override 2 types of temptations, termed doing wrong and not doing right. We report a series of 5 studies designed to test the reliability and validity of the scale. As hypothesized, high DSC predicts distant future orientation and low DSC predicts deviant behaviors such as aggression, alcohol misuse, and aberrant driving. DSC also predicts task performance among resource-depleted participants. Taken together, these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…In fact, the widely used BSCS (Tangney et al, 2004) already incorporated an initiatory component, based on the comprehensive review by Baumeister, Heatherton, and Tice (1994) that distinguishes four inhibitory components (control thoughts, emotions, impulses, and maladaptive habits) and one initiatory component (regulate performance) of self-control. Recent research on trait self-control (De Ridder, De Boer, Lugtig, Bakker, & Van Hooft, 2011;Ein-Gar & Sagiv, 2014;Hoyle & Davisson, 2016) corroborates the notion that self-control encompasses both inhibition and initiation components with self-control by inhibition involving the conscious overriding of a tendency to engage in goal-inconsistent behaviour while self-control by initiation involves consciously acting in a goal-consistent manner despite initial reluctance. Previous research on state self-control has also provided some evidence that the initiation of a desired response is an important aspect of successful performance, as is for example witnessed by studies using the Stroop task: successful completion of this task not only requires inhibition of a specific response but also to replace this response tendency with another response (Richeson & Shelton, 2003;cf.…”
mentioning
confidence: 82%
“…In fact, the widely used BSCS (Tangney et al, 2004) already incorporated an initiatory component, based on the comprehensive review by Baumeister, Heatherton, and Tice (1994) that distinguishes four inhibitory components (control thoughts, emotions, impulses, and maladaptive habits) and one initiatory component (regulate performance) of self-control. Recent research on trait self-control (De Ridder, De Boer, Lugtig, Bakker, & Van Hooft, 2011;Ein-Gar & Sagiv, 2014;Hoyle & Davisson, 2016) corroborates the notion that self-control encompasses both inhibition and initiation components with self-control by inhibition involving the conscious overriding of a tendency to engage in goal-inconsistent behaviour while self-control by initiation involves consciously acting in a goal-consistent manner despite initial reluctance. Previous research on state self-control has also provided some evidence that the initiation of a desired response is an important aspect of successful performance, as is for example witnessed by studies using the Stroop task: successful completion of this task not only requires inhibition of a specific response but also to replace this response tendency with another response (Richeson & Shelton, 2003;cf.…”
mentioning
confidence: 82%
“…Integrating these studies into a general theoretical framework, we suggest that self-control can be viewed as a process reflecting an inner struggle and an intentional effort that individuals invest to override the desire to perform actions or inactions that promise immediate gratification in the present, yet at the same time promote future negative outcomes. Ein-Gar and colleagues (Ein-Gar, Goldenberg, & Sagiv, 2008;Ein-Gar & Sagiv, 2011;Ein-Gar & Steinhart, 2011) have suggested that such actions can be categorized into two general types: "doing wrong" (impulsive, self-satisfying actions that harm one's future well-being, such as eating a cake while on a diet, buying products one cannot afford), and "not doing right" (actions of procrastinating about what needs to be done and thus, once again, risking one's future wellbeing, such as failing to exercise, use sunscreen or write an important paper).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…For example, in a recent study, Ein-Gar and Steinhart (2011) use this scale to predict persistence in monotonous, boring tasks and to predict impulsive buying and the consumption of hedonic food. (For complete details of the scale construction and validation, see Ein-Gar et al, 2008;Ein-Gar & Sagiv, 2011;Ein-Gar & Steinhart, 2011. ) 3.1.3.2.…”
Section: Instrumentsmentioning
confidence: 99%
“…Pretest participants underwent either the high-or the low self-control manipulation, then completed a filler task, and finally completed the Dispositional Self-Control (DSC) scale as a manipulation check. The DSC scale (Ein-Gar, Goldenberg, & Sagiv, 2008, Ein-Gar et al, 2012Ein-Gar & Sagiv, 2014;Ein-Gar & Steinhart, 2011) consists of 17 items (α = .88) measuring participants' tendency to overcome temptations or to yield to them. Participants reported their agreement with each statement on a 5-point Likert scale ranging from 1 ("not at all") to 5 ("very much").…”
Section: Self-control Manipulationmentioning
confidence: 99%
“…The DSC scale (Ein‐Gar et al, 2008, 2012; Ein‐Gar & Sagiv, 2014; Ein‐Gar & Steinhart, 2011) was used to measure participants' level of self‐control (α = .89).…”
Section: Introductionmentioning
confidence: 99%